10 – ; 10 years of transition in Ukraine agriculture: An analysis of productivity and efficiency of enterprises - Aleksej Lissitsa; Martin Odening; Tamara Babiéceva (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2003)
" " (. total factor productivity, TFP) . (. data envelopment analysis, DEA), - - (. Malmquist productivity change index, MPI) 1990 1999 . , 6 % , , 42 %. . , , , , . , / , . – – This paper analyzes efficiency and total factor productivity (TFP) change of large agricultural enterprises during their transition to a market economy in Ukraine. In this case the efficiency is calculated by data envelopment analysis and the productivity change is measured by the Malmquist Productivity Change Index in the period between 1990 and 1999. On average, TFP declined by 6% annually, dropping a total 42%. The main reason for the observed TFP decline is a decrease in technical efficiency, which is found to be remarkably significant. At the same time there is a high variation among individual enterprises: their distribution of efficiency scores widens, which indicates that the farms diverge with respect to their economic performance. The Tobit regression analysis is conducted where the efficiency scores are related to factors such as farm type, farm size, initial conditions and legal form.
urn:nbn:de:gbv:3:2-23274
Keywords: Q12; D2; O1; O4; P3; 630; -; Efficiency; Total Factor Productivity; Data Envelopment Analysis; Malmquist Productivity Change Index; Transition; Ukraine; Landwirtschaft; Produktivität; Technische Effizienz; Data-Envelopment-Analyse; Schätzung; Ukraine